Exploring the Gelation Mechanisms and Cytocompatibility of Gold (III)-Mediated Regenerated and Thiolated Silk Fibroin Hydrogels - Laomeephol, Chavee (Biomolecules, 2020)
Accelerating the gelation of silk fibroin (SF) solution from several days or weeks to minutes or few hours is critical for several applications (e.g., cell encapsulation, bio-ink for 3D printing, and injectable controlled release). In this study, the rapid gelation of SF induced by a gold salt (Au(3+)) as well as the cytocompatibility of Au(3+)-mediated SF hydrogels are reported. The gelation behaviors and mechanisms of regenerated SF and thiolated SF (tSF) were compared. Hydrogels can be obtained immediately after mixing or within three days depending on the types of silk proteins used and amount of Au(3+). Au(3+)-mediated SF and tSF hydrogels showed different color appearances. The color of Au-SF hydrogels was purple-red, whereas the Au-tSF hydrogels maintained their initial solution color, indicating different gelation mechanisms. The reduction of Au(3+) by amino groups and further reduction to Au by tyrosine present in SF, resulting in a dityrosine bonding and Au nanoparticles (NPs) production, are proposed as underlying mechanisms of Au-SF gel formation. Thiol groups of the tSF reduced Au(3+) to Au(+) and formed a disulfide bond, before a formation of Au(+)-S bonds. Protons generated during the reactions between Au(3+) and SF or tSF led to a decrease of the local pH, which affected the chain aggregation of the SF, and induced the conformational transition of SF protein to beta sheet. The cytocompatibility of the Au-SF and tSF hydrogels was demonstrated by culturing with a L929 cell line, indicating that the developed hydrogels can be promising 3D matrices for different biomedical applications.